2019
DOI: 10.5603/pjnns.a2019.0052
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drugs in epilepsy

Abstract: The prevalence of various psychiatric disorders in people with epilepsy is high, with psychoses affecting 2-9% of patients. Antipsychotic drugs have been identified as increasing the risk of epileptic seizures. For first-generation antipsychotics such a risk appears to be relatively low, with the exception of chlorpromazine. Among second-generation antipsychotics, clozapine use carries the highest risk of seizure induction, while risperidone, quetiapine, amisulpride, and aripiprazole seem to pose a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…Although there are published reports about antipsychotics and associated risk of seizures, most of these are descriptive studies. Therefore, a causal relation between antipsychotics use and development of seizure has not been unequivocally confirmed, particularly in individuals with ASD (Górska et al, 2019 ; Grover et al, 2015 ; Hedges et al, 2003a , 2003b ; Williams & Park, 2015 ). It should be noted in the light of evidence that around 50% of the prescribed antipsychotics for individuals with ASD are not approved in the UK for use in this population, which may indicate an off-label medication prescribing (Alfageh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are published reports about antipsychotics and associated risk of seizures, most of these are descriptive studies. Therefore, a causal relation between antipsychotics use and development of seizure has not been unequivocally confirmed, particularly in individuals with ASD (Górska et al, 2019 ; Grover et al, 2015 ; Hedges et al, 2003a , 2003b ; Williams & Park, 2015 ). It should be noted in the light of evidence that around 50% of the prescribed antipsychotics for individuals with ASD are not approved in the UK for use in this population, which may indicate an off-label medication prescribing (Alfageh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have not taken account of medication dose. There is considerable evidence from the literature that, for medications that are associated with increased seizure risk, the risk is very much related to medication dose (Górska et al, 2019 ; Grover et al, 2015 ; Varma et al, 2011 ). Other reports have suggested that low-dose antipsychotic medication, as used to treat anxiety and/or behavioural problems in young people with ASD might not be associated with an increased risk of seizures but this leaves the possibility that higher antipsychotic doses, such as those used to treat psychosis or bipolar disorder might be associated with an increased seizure risk.…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic drugs have been found to increase the risk of epileptic seizures. Second-generation antipsychotics, especially clozapine carry a higher risk than the first-generation antipsychotics [39]. Seizures occur in one to five of every 10 people who have had a traumatic brain injury (TBI), depending on the location of injury in the brain [40].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Es zeigt sich jedoch, dass das Anfallsrisiko in der Gruppe der antipsychotischen Medikamente unterschiedlich ist. Vor allem bei Neuroleptika der zweiten Generation wie Clozapin ist das Risiko im Vergleich zu anderen antipsychotischen Medikamenten erhöht [49]. Es treten in erster Linie tonisch-klonische Anfälle auf, wobei auch andere Anfallstypen vorkommen können [50].…”
Section: Neuroleptikaunclassified
“…Insgesamt ist das Risiko von Anfällen unter Clozapin dosisabhängig und bis zu 4,4 % bei ≥ 600 mg Tagesdosis [51]. Um das Anfallsrisiko gering zu halten, sind eine möglichst niedrige Anfangsdosis, ein langsames Steigern der Medikation, regelmäßige Blutspiegelkontrollen und eine möglichst niedrig dosierte Dauertherapie anzustreben [49]. Sollte es zu Anfällen unter Neuroleptika kommen, sollte zunächst, wenn möglich, die Dosis verringert werden oder auf alternative Antipsychotika mit geringer Anfallsrate umgestellt werden [51,52].…”
Section: Neuroleptikaunclassified